(untitled) (Studia Prawnicze / The Legal Studies, 1993)
Dziecko mogłoby realizować prawo do znajomości własnego pochodzenia de lege lata jedynie na drodze powództwa o ustalenie ojcostwa. Dotyczyłoby to tylko dzieci, których ojcostwo nie zostało ustalone. Dziecko, którego ojcem jest mąż matki, najpierw musiałoby skorzystać z instytucji zaprzeczenia ojcostwa (art. 70 k.r.o.), wykazując, że mąż matki mógł być jego ojcem, natomiast dziecko uznane - wytoczyć powództwo o unieważnienie uznania, powołując się i udowadniając fakt, że mężczyzna, który je uznał, nie jest jego ojcem. Następnie należałoby wystąpić do sądu z żądaniem ustalenia ojcostwa. Dziecko poczęte wskutek sztucznego zapłodnienia byłoby w takim procesie w szczególnie trudnej sytuacji. Jak wiadomo - w tego typu procesach osoba żądająca ustalenia ojcostwa wykazuje fakt, iż mężczyzna w okresie koncepcyjnym obcował z matką dziecka (art. 85 paragraf 1 k.r.o.). Faktu tego nie można (w omawianej sytuacji) udowodnić, gdyż do obcowania matki dziecka a dawcą nasienia nie doszło. Pozostaje więc wykazanie w jakiś inny sposób, że dawca nasienia jest ojcem dziecka. W świetle obowiązujących przepisów jest to praktycznie niemożliwe, ponieważ nie można wskazać mężczyzny, który w okresie koncepcyjnym obcował z matką dziecka. A child could only realise the right to know his or her own origins de lege lata through a legal claim intended to establish paternity. This would only apply to children whose paternity has not been established. A child fathered by the husband of the mother would first have to use the paternity denial institution (Article 70 of the Family and Guardianship Code) by indicating that the husband of the mother could be his or her father, while an acknowledged child - raise a claim to invalidate the acknowledgement by invoking and justifying the fact that the male who acknowledged his or her is not his or her father. It would then be necessary to apply to the court to establish paternity. A child conceived through artificial insemination would be in a particularly difficult position in such a proceeding. As it is known - in this type of proceedings, the person requesting to determine paternity proves the fact that the man had an intercourse with the mother of the child during the conception period (Article 85(1) of the Family and Guardianship Code). This fact cannot (in the discussed situation) be proven, as there was no intercourse between the mother of the child and the sperm donor. Thus, it has to be proven otherwise that the sperm donor is the father of the child. This is practically impossible under the current legislation, as it is not possible to identify a man who had intercourse with the mother of the child during the conception period.